Genome‐wide Identification and Structural Analysis of Pyrophosphatase Gene Family in Cotton. Issue 4 (1st July 2016) - Zhao, Xiaojie; Lu, Xuke; Yin, Zujun; Wang, Delong; Wang, Junjuan; Fan, Weili; Wang, Shuai; Zhang, Tianbao; Ye, Wuwei
Abstract : Pyrophosphatase is a hydrolytic enzyme that utilizes pyrophosphate as a substrate. H + ‐PPase, an important proton pump on the vacuolar membrane, plays an important role in regulating cell expansion, H + electrochemical gradient, and secondary active transport of inorganic ions, organic acids and saccharides. Under low temperature, drought, high NaCl concentration, and hypoxia, H + ‐PPase gene expression is promoted to maintain the intracellular balance and enhance the ability of stress resistance in plants. The GhVP gene family is a class of H + ‐PPase genes in Gossypium hirsutum L. The present study identified 13 H + ‐PPase genes from diploid Gossypium raimondii Ulbrich (genome D) and Gossypium arboreum L. (genome A), and analyzed their genetic structures and systematic evolution. The 13 H + ‐PPase genes, including six and seven from diploid G. arboreum and G. raimondii, respectively, were obtained with GhVP as a reference. The H + ‐PPase genes belong to a relatively conserved family in plant evolution. Phylogenetic analysis indicated that the genes of the same species showed high sequence similarities and relatively close genetic relationships. Gene structural analysis indicated that most of the H + ‐PPase genes had 7–8 exons, with a few having a variable number (1–14) of exons. By analyzing the conserved domain, the H + ‐PPase genes showed several relatively conserved structural domains, such as a myristyl site, casein kinase site II, and protein kinase phosphorylation site. These findings provide a basis for the further characterization of the H + ‐PPase gene function in cotton. Analysis by qRT‐PCR showed that a different expression level of gene members in the V‐PPase family existed in different tissues; for example, gene expression was highest in leaves and lowest in fibers to suggest that V‐PPase expression is tissue‐specific. Moreover, with the salt stress intensity increasing, the changes of expression level of the V‐PPase genes were different.